Combined in situ Physical and ex-situ Biochemical Approaches to Investigate in vitro Deconstruction of Destarched Wheat Bran by Enzymes Cocktail Used in Animal Nutrition - Deshors, Marine; Guais, Olivier; Neugnot-Roux, Virginie; Cameleyre, Xavier; Fillaudeau, Luc; Francois, Jean Marie (Frontiers in Bioengineering and Biotechnology, 2019)
Wheat bran is a foodstuff containing more than 40% of non-starch polysaccharides (NSPs) that are hardly digestible by monogastric animals. Therefore, cocktails enriched of hydrolytic enzymes (termed NSPases) are commonly provided as feed additives in animal nutrition. However, how these enzymes cocktails contribute to NSPs deconstruction remains largely unknown. This question was addressed by employing an original methodology that makes use of a multi-instrumented bioreactor that allows to dynamically monitor enzymes in action and to extract in-situ physical and ex-situ biochemical data from this monitoring. We report here that the deconstruction of destarched wheat bran by an industrial enzymes cocktail termed Rovabio® was entailed by two concurrent events: a particles fragmentation that caused in less than 2 h a 70% drop of the suspension viscosity and a solubilization that released less than 30 % of the wheat bran NSPs. Upon longer exposure, the fragmentation of particles continued at a very slow rate without any further solubilization. Contrary to this cocktail, xylanase C alone caused a moderate 25 % drop of viscosity and a very weak fragmentation. However, the amount of xylose and arabinose from solubilized sugars after 6 h treatment with this enzyme was similar to that obtained after 2 h with Rovabio®. Altogether, this multi-scale analysis supported the synergistic action of enzymes mixture to readily solubilize complex polysaccharides, and revealed that in spite of the richness and diversity of hydrolytic enzymes in the cocktail, the deconstruction of NSPs in wheat bran was largely incomplete.